2023
DOI: 10.21470/1678-9741-2021-0333
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Based Differences in One-Year Outcomes After Mitral Valve Repair for Infective Endocarditis

Zeinab Mohseni Afshar,
Feridoun Sabzi,
Maria Shirvani
et al.

Abstract: Introduction This study was aimed to evaluate the sex-based differences in baseline characteristics and one-year outcomes of men and women undergoing mitral valve repair for infective endocarditis. Methods This cross-sectional study was performed at Imam Ali Hospital affiliated with the Kermanshah University of Medical Science. From March 21, 2014, to October 21, 2021, all patients who underwent mitral valve repair for infective endocarditis were enrolled in this study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 24 publications
(30 reference statements)
1
6
0
Order By: Relevance
“…Two studies found that females typically had more comorbidities, supported by other studies' findings [12,14]. Females were more likely to have diabetes, atrial fibrillation, arterial hypertension, hypercholesterolemia, take immunosuppressants, chronic lung disease, malignancy, previous valve replacement, and psychiatric disorders like depression/bipolar disorder [14,21,26,27,31,32,39,41,43]. However, when this was crossed with females who had type 2 diabetes mellitus, females specifically had a higher incidence of dementia, atrial fibrillation, previous mitral valve disease, and previous tricuspid valve disease [43].…”
Section: Comorbiditiesmentioning
confidence: 66%
See 4 more Smart Citations
“…Two studies found that females typically had more comorbidities, supported by other studies' findings [12,14]. Females were more likely to have diabetes, atrial fibrillation, arterial hypertension, hypercholesterolemia, take immunosuppressants, chronic lung disease, malignancy, previous valve replacement, and psychiatric disorders like depression/bipolar disorder [14,21,26,27,31,32,39,41,43]. However, when this was crossed with females who had type 2 diabetes mellitus, females specifically had a higher incidence of dementia, atrial fibrillation, previous mitral valve disease, and previous tricuspid valve disease [43].…”
Section: Comorbiditiesmentioning
confidence: 66%
“…Two studies found that females typically had more comorbidities, supported by other studies' findings [12,14]. Females were more likely to have diabetes, atrial fibrillation, arterial hypertension, hypercholesterolemia, take immunosuppressants, chronic lung disease, malignancy, previous valve replacement, and psychiatric disorders like depression/bipolar disorder [14,21,26,27,31,32,39,41,43].…”
Section: Comorbiditiesmentioning
confidence: 73%
See 3 more Smart Citations